Forms and Functions of Sarcasm in CNBC's YouTube Comments on Global Recession - Nafisah, Dzurrotun (Journal of Literature, Linguistics, & Cultural Studies, 2024)
The purpose of this study is to determine the form and function of sarcastic comments contained in the CNBC Television Channel comment section, so that the results of the study can solve the phenomenon of a possible global recession in 2023 and provide a broader understanding that sarcasm can make it easier for people to criticize an issue. The researcher only selected videos that discussed the potential 2023 global recession along with its causes and consequences. We used a quasi qualitative method. Although this method cannot be said to be qualitative, it still allows the effective use of theory as a research tool. The theory used is Elisabeth Camp's theory (2011) to determine the form of sarcasm and Gorys Keraf's theory (2010) to determine the function of sarcastic comments. The result of this research is that from 12 YouTube videos, there are 83 data consisting of 6 forms of propositional sarcasm, 48 forms of lexical sarcasm, 12 forms of prefix sarcasm, and 17 forms of illocutionary sarcasm. Then, from 10 functions of sarcastic comments, only 6 functions were found: rejection, conveying affirmation, conveying information, expressing opinions, and submitting questions. From the results, it shows that netizens explicitly show disagreement and prefer to express opinions based on the subjective truth of the party concerned in the video. Future researchers are suggested to explore variations in data and to dig deeper into the differences in the use of sarcasm based on age, gender, and cultural background.